2012
DOI: 10.1038/bmt.2012.155
|View full text |Cite
|
Sign up to set email alerts
|

Juvenile metachromatic leukodystrophy 10 years post transplant compared with a non-transplanted cohort

Abstract: Metachromatic leukodystrophy (MLD) is a rare inborn error of metabolism leading to severe neurological symptoms and early death. Hematopoietic SCT (HSCT) is considered a treatment option, but results are inconsistent and comparison with natural history is practically missing. We compare a girl with juvenile MLD 10 years after allogeneic HSCT not only with her untreated sister, but also with a large cohort of untreated patients. The girl received HSCT at the age of 5 years when first motor signs appeared. Over … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
44
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(49 citation statements)
references
References 24 publications
5
44
0
Order By: Relevance
“…But the further progression of demyelination, and especially the involvement of specific WM areas, seems to correlate well with specific aspects of clinical deterioration. In the evaluation of therapeutic effects and cerebral changes on follow‐up, the demyelination load was already demonstrated to be more sensitive than the MRI scoring system 8, 28. Still, the sensitivity and specificity of new (more myelin‐specific) MRI parameters might be important to evaluate further in detecting functionally relevant WM changes in the brain as suggested recently, for example, diffusion‐weighted imaging, MR spectroscopy, magnetization transfer imaging, myelin water imaging, cortical thickness determination, and GM/WM volumetry 12, 29, 30, 31…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…But the further progression of demyelination, and especially the involvement of specific WM areas, seems to correlate well with specific aspects of clinical deterioration. In the evaluation of therapeutic effects and cerebral changes on follow‐up, the demyelination load was already demonstrated to be more sensitive than the MRI scoring system 8, 28. Still, the sensitivity and specificity of new (more myelin‐specific) MRI parameters might be important to evaluate further in detecting functionally relevant WM changes in the brain as suggested recently, for example, diffusion‐weighted imaging, MR spectroscopy, magnetization transfer imaging, myelin water imaging, cortical thickness determination, and GM/WM volumetry 12, 29, 30, 31…”
Section: Discussionmentioning
confidence: 99%
“…Given the variability in the clinical course, this is not only important for patient counseling, but also for treatment decision as discussed above. It has been shown that the treatment effect of HSCT, currently the only clinically available treatment option for juvenile MLD, might take some time to have an effect 8, 32, 33. Therefore, it seems essential to have additional parameters in order to predict whether the individual patient will deteriorate rapidly or might still have a wide enough window of opportunity for HSCT.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…1 HSCT is currently the only treatment in clinical use for late-juvenile and adult MLD, but the long-term results that have been published are few and inconclusive. [6][7][8][9][10][11][12][13] …”
Section: Introductionmentioning
confidence: 99%